Observation of B → ψ (2S)K S0π+π- and B s0 → ψ (2S)K S0 decays - KAYA, MİTHAT (My University, 2022)
© 2022, The Author(s).Using a data sample of s=13TeV proton-proton collisions collected by the CMS experiment at the LHC in 2017 and 2018 with an integrated luminosity of 103fb-1, the Bs0→ψ(2S)KS0 and B0→ψ(2S)KS0π+π- decays are observed with significances exceeding 5 standard deviations. The resulting branching fraction ratios, measured for the first time, correspond to B(Bs0→ψ(2S)KS0)/B(B0→ψ(2S)KS0)=(3.33±0.69(stat)±0.11(syst)±0.34(fs/fd))×10-2 and B(B0→ψ(2S)KS0π+π-)/B(B0→ψ(2S)KS0)=0.480±0.013(stat)±0.032(syst), where the last uncertainty in the first ratio is related to the uncertainty in the ratio of production cross sections of Bs0 and B mesons, fs/ fd.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)